DISKUSI KEUANGAN PENDIDIKAN : Optimalisasi Dana Alokasi Khusus (DAK Fisik dan Non Fisik-BOS) Dalam Peningkatan Mutu Pendidikan - Abdul, Abdul Rachim; Habibi, Muhammad (Manajemen Pendidikan Program Doktor, 2021)
The Special Allocation Fund or DAK as an important element in the implementation and improvement of the quality of education is currently one of the recess agendas for members of the House of Representatives of the Republic of Indonesia (DPRD RI) and an important recess agenda. Where according to the Law of the Republic of Indonesia Number 33 of 2004 concerning the Financial Balance between Central Finance and Regional Finance, Article 1 number 23 explains that the Special Allocation Fund, hereinafter referred to as DAK, is a fund sourced from APBN revenues allocated to certain regions with the aim of helping fund special activities which are regional affairs and in accordance with national priorities. The allocation of DAK itself exists for physical and non-physical development. Physical DAK The two types of DAK are a source of finance for the implementation and improvement of the quality of education, particularly in the province of East Kalimantan. The purpose of the discussion is to generate; (a) a number of important points from guest speakers and participants or discussion audiences on education finance DAK, and (b) found a number of solutions that are thought to support the strengthening, utilization and management of education finance DAK. The planned method is a face-to-face discussion that refers to the health protocol that applies during the PKM implementation later. The outputs on the agenda are scientific articles published in unaccredited national journals. The results of the implementation of PKM education discussions which are part of the educational workshop activities, it can be concluded that (1) The education system and local government administration are in line with a number of regulations, one of which is the Law of the Republic of Indonesia Number 33 of 2004 concerning Financial Balance between Central Finance and Finance Regions that declare the existence of DAK, including in the field of education; (2) During the Covid-19 pandemic, the issue of education, funding, and the impact of Covid-19 became very hot to discuss, especially the increasing burden on parents, while the burden on teachers was seen to be reduced; and (3) The problem in Samarinda City is that the number of DAK for Education in 2021 tends to be small compared to other cities in Indonesia. Therefore, it is necessary to optimize DAK factually, both in the form of physical and non-physical proposals, because the proposal determines the size of the DAK for education in an area.